Lumbar spondylodiscitis with pre-and paraspinal abscess: Major complication of central venous catheter-related infection in a haemodialysis patient - Ferreira,Emanuel (2014)
Vertebral osteomyelitis has been seen with increasing frequency in haemodialysis patients. We describe a case of spondylodiscitis in a patient undergoing haemodialysis with three previous episodes of catheterrelated infections. The poor response to medical treatment and the formation of a large abscess close to the aorta led to the need for surgical intervention. We highlight the need for a multidisciplinary approach to the treatment of this serious complication of the use of central venous catheters in haemodialysis